The First Kodokan Judo Kata International Competition and its Katas - Gatling, Lance (Revista de Artes Marciales Asiáticas, 2012)
In October 2007, the Kodokan hosted the first global Kodokan Judo forms (katas) competition in Tokyo. This article briefly outlines the background of the competition, the competitors, the motivations for this competition, the historical development of judo katas, and their importance to the correct study of judo. Sources include personal kata study, observation of the two-day competition, interviews, and English and Japanese texts. Judo katas are an often neglected aspect of judo training, but there is growing interest in this classical, important part of the study of judo. The katas preserve the oldest techniques of judo, including its classical jujutsu roots.